ANALISIS PENERAPAN PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DI KABUPATEN MALANG - Anggraini, Elga (Jurnal Mahasiswa Perpajakan, 2015)
The application of BPHTB collection in Malang Regency is based on the Standard Operational Procedure (SOP) of BPHTB collection that has been regulated through Decree of Regent. The potential of BPHTB in Malang Regency is determined based on the extent of territory of Malang Regency with 13 objects subjected to BPHTB. The implementation of BPHTB collection is influenced by several factors. The supporting factor is a President Program to build people housings that may increase the potential of BPHTB and also other related programs. The constraining factor is lack of obedience from taxpayer which causes less effectiveness of BPHTB collection. Result of BPHTB collection in PAD of Malang Regency is quite favorable, and the implementation of BPHTB collection has been very effective because the realization rate is beyond 100 % of the predetermined target. Keywords: the Analysis over BPHTB Collection, BPHTB, the Analysis over the Application of Collecting. ABSTRAK Penerapan pemungutan BPHTB di Kabupaten Malang didasarkan pada Standar Oprasional Prosedur (SOP) pemungutan BPHTB yang telah diatur dalam Peraturan Bupati (Perbup). Potensi dari BPHTB yang ada di Kabupaten Malang ditentukan berdasarkan luas wilayah Kabupaten Malang dengan 13 objek yang dikenakan BPHTB. Pelaksanaan pemungutan BPHTB terdapat beberapa faktor yang mempengaruhi diantaranya faktor pendukung yang berupa program presiden yang ingin membangun rumah untuk rakyat yang nantinya berpotensi BPHTB dan beberapa faktor lain sedangkan, faktor penghambar yang ada salah satunya disebabkan oleh ketidak patuhan wajib pajak yang menyebabkan tidak efektifnya waktu pemungutan BPHTB. Hasil dari pemungutan BPHTB untuk PAD Kabupaten Malang cukup tinggi dan dalam pelaksanaanya menunjukkan hasil sangat efektifÂ  karena realisasi diatas 100% dari target yang ditetapkan. Kata Kunci: Analisis Pemungutan BPHTB, BPHTB, Analisis Penerapan Pemungutan.